Cyberterrorism : an analysis of law in Oman with special reference to the Islamic law - Almashrafi, Hamood Abdullah Hamood (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
Cyberterrorism is one of the most pressing threats and challenges of the time. It is interesting that the cyber environment aspires improvement and development in every public and private sector. Obviously the development of information and communication technology brings ease and comfort in the lives of the people. But the same has given rise to cyberterrorism activities like intrusion into civil aviation, defense and healthcare systems, as well as critical information theft and security threats by computer hacking. It is a fact that the whole world faces a serious threat of cyberterrorism which requires immediate attention. The threat of cyberterrorism is getting serious with the passage of time because the cyber-technology itself is unable to provide complete protection to the critical infrastructure. On the other hand, it is a fact that the international community is trying to address the imminent threat of cyberterrorism with laws and legislation. The research analyzed the scope and nature of cyberterrorism and how different countries including the US, the Netherlands, the European Union and the Sultanate of Oman are dealing with the subject matter legally. The researcher also highlighted the salient features of legal system of Oman including the Civil Law and the Islamic Law on cyberterrorism. A library-based approach was adopted to discuss the scope and nature of cyberterrorism and the legal mechanism of the US, the Netherlands and the Sultanate of Oman to combat cyberterrorism. Furthermore, critical analysis has been done to highlight the drawbacks and loopholes in the legal system. In addition, an exposition has been made of the SharÊÑah about cyberterrorism which is stated in the Qur'an and Sunnah with special reference to the concept of cyberterrorism in the light of SharÊÑah principles. The researcher opined that the gradual legislation in the world at national, regional and international level and mutual co-operation within law enforcement agencies are one of the best options to deal with the threat of cyberterrorism. Finally, there is a need to bring the whole world under a common international legal platform to help combat cyberterrorism.